A naturalistic comparison of two inpatient treatment protocols for adults with anorexia nervosa: Does reducing duration of treatment and external controls compromise outcome?. Issue 9 (13th August 2019) - Paquin Hodge, Chloé; Gauvin, Lise; St‐Hilaire, Annie; Israel, Mimi; Azzi, Michelle; Kahan, Esther; Thaler, Lea; Dansereau, Eve; Steiger, Howard
Abstract: Objective: Although hospitalization is sometimes necessary when treating individuals with anorexia nervosa, the available literature provides limited guidance to inform decisions surrounding optimal components or duration of inpatient treatments. We report observational data comparing outcomes of two inpatient treatments. The first was longer and more strictly structured around a Contingency Management Protocol (CMP) emphasizing external incentives for achieving weight‐restoration goals; the second was a shorter Autonomy Support Protocol (ASP) that progressively increased patient autonomy around meal management without external incentives. Method: We compared data from 41 patients who participated in the ASP to a historical sample of 41 patients treated using the CMP. At admission, discharge, and post‐treatment follow‐up, participants completed the Eating Disorder Examination Questionnaire and the Behavior and Symptom Identification Scale‐32, and we measured height and weight to compute body mass index. Results: Multilevel modeling analyses that controlled for time in treatment and time in follow‐up indicated the two protocols yielded equivalent in‐treatment gains and post‐treatment loss of gains. Discussion: Our results indicate that shorter inpatient stays emphasizing autonomous control over eating behavior may yield outcomes that are equivalent to those of lengthier, more stringent, and more costly approaches implicating external incentives and controls.